Frankish manuscripts the seventh to the tenth century - Nees, Lawrence 1949- (A survey of manuscripts illuminated in France, 2022)
Frankish Manuscripts' covers the earliest period in this series devoted to manuscripts illuminated in France. The two volumes explore those manuscripts that originate in the period before the kingdom of France emerged at the end of the tenth century. From the seventh to the tenth century most of modern France was ruled by kings of the Franks, from dynasties known as Merovingian and Carolingian, whose territories also included significant portions of other modern nations, especially the Low Countries, Germany, Switzerland and Austria.00The introductory essay in Volume I offers an overview of salient issues in this creative period, formative for later medieval manuscripts produced in France and elsewhere, in the former Frankish territories and beyond; the volume includes 341 photographs from the manuscripts in the catalogue, the great majority reproduced in colour. Volume II comprises a detailed catalogue of 100 manuscripts from this large region, each with a detailed description, an interpretive commentary focused on the decoration of the text as well as illustrations, and a survey of previous scholarly literature, including digital access when available. The catalogue includes some of the most famous early medieval manuscripts, decorated with luxury materials and exceptionally beautiful script, ornament and illustrations. In the spirit of a survey intended to show the range of Frankish illumination, it also includes manuscripts of ancient and contemporary poems, scientific works, commentaries, a cookbook, and one manuscript in a vernacular language. Together, these two volumes provide the most comprehensive survey of manuscript illumination in Francia, its large corpus of illustrations making the manuscripts more readily available for study not only by scholars of illumination but also by others interested in early medieval culture